(untitled) (REMUNOM, 2024)
Enamel hypomineralization is a dental condition that involves a reduction in the mineralization of tooth enamel, making it a more fragile structure and susceptible to damage. This dental condition has attracted increasing interest due to its prevalence and significant clinical implications. This condition mainly affects molars and incisors, resulting in a decrease in the mineralization of the enamel of these teeth. The aim of this study was to assess the knowledge of dental students at the Federal University of Campina Grande, Patos campus, Paraíba, on this subject. Data was collected using a questionnaire addressed to students from the 7th to 10th periods of the Dentistry course, covering questions about the prevalence, etiology, diagnosis and treatment of the condition. With regard to diagnosis, in figure 1, which asked about the correct diagnosis of the condition, 34 (39.5%) of the people got it right, in figure 2, which asked about the correct way to diagnose the case and what the probable diagnosis was, 47 students (54.7%) got it right, and in figure 3, which asked about the most suitable treatment for the condition presented, there were the highest number of correct answers, in which 74 of the people (74.4%) got it right. Although the majority of students claim to be aware of IMH, it is still a topic unknown to a significant number of dental students, especially when it comes to diagnosing the condition. Therefore, academic training should improve the approach and overcome this difficulty. Keywords: Enamel hypomineralization; HMI; Dental enamel development defects; Tooth enamel.